การยืดอายุเส้นก๋วยเตี๋ยวสด - มหัทธนทวี กาญจนา; คงบรรเจิดสกุล วชิรา (Journal of Food Technology, Siam University, 2015)
การเสียของเส้นก๋วยเตี๋ยวสดมักเกิดจากรา ในงานวิจัยนี้ทาการแยกราที่เป็นสาเหตุของปัญหาจากก๋วยเตี๋ยวเส้นเล็กสด ได้ทั้งหมด 9 ชนิด ที่มีลักษณะของเส้นใย รูปร่างการเรียงตัวและลักษณะของสปอร์ที่แตกต่างกันจากลักษณะสัณฐานดังกล่าวทำให้สามารถจำแนกชนิดของราได้ 7 ชนิด ได้แก่ Aspergillus sp. K1, Aspergillus sp. K2, Humicola sp., Trichosporonides sp., Basipetospora sp., Gilocephalis sp.และ Penicillium sp. จากการศึกษาผลของการเติมโซเดียมเบนโซเอตความเข้มข้น 1,000 ppm เพื่อยับยั้งการเจริญของรา และค่าความเป็นกรด-ด่างที่มีผลต่อประสิทธิภาพการทำงานของโซเดียมเบนโซเอต ในระดับจานเพาะเชื้อที่ใช้น้าแป้งข้าวเจ้าเป็นอาหารเลี้ยงเชื้อ พบการเจริญของราทั้ง 9 ชนิด ในจานเพาะเชื้อที่ไม่เติมและเติมโซเดียมเบนโซเอตภายใน 1 วัน เมื่อเติมโซเดียมเบนโซเอตและปรับค่า pH ด้วยกรดซิตริกที่ระดับ 3.5 และ4.0 พบว่ามีผลต่อการยับยั้งการเจริญของราตั้งแต่ 2 วัน ถึงมากกว่า 20 วัน เมื่อทดสอบกับก๋วยเตี๋ยวเส้นเล็กสดที่เตรียมขึ้นเองโดยเติมโซเดียมเบนโซเอต 1,000 ppm และปรับค่า pH ด้วยกรดซิตริก เป็น 3.5 และ 4.0 เปรียบเทียบกับตัวอย่างควบคุมที่มีและไม่มีการเติมโซเดียมเบนโซเอต พบว่าอายุการเก็บรักษาเป็น 15 6 4 และ 2 วันตามลำดับ การทดสอบทางประสาทสัมผัสด้านการยอมรับโดยรวมของก๋วยเตี๋ยวที่ปรับค่า pH เป็น 4 ไม่แตกต่างจากเส้นก๋วยเตี๋ยวที่ไม่มีการปรับค่า pH ผลการทดลองดังกล่าวจะเป็นแนวทางให้กับผู้ประกอบการได้นาไปประยุกต์ใช้เพื่อการยืดอายุการเก็บรักษาเส้นก๋วยเตี๋ยวสด Shelf life extension of fresh noodle The deterioration of fresh noodle was mainly caused by fungi. In this study, 9 types of fungi were isolated from spoiled fresh noodle. The physical morphology (i.e. hyphae, septum or non septum of hyphae and shape of spore) was used as tentative identification of these fungi. There were 7 types of identified fungi, Aspergillus sp. K1, Aspergillus sp. K2, Humicola sp., Trichosporonides sp., Basipetospora sp., Gilocephalis sp. and Penicillium sp. The efficiency of sodium benzoate 1,000 ppm as preservative agent in fresh noodle was studied by varying the pH value of noodle at 3.5 and 4.0. The growth of the fungi on culture plate was studied with rice paste as a culture media. It was found that all 9 types of fungi were noticed after one day on the culture plate both with and without added sodium benzoate. By adjusting the pH of culture media to 3.5 and 4.0 with citric acid, the efficiency of sodium benzoate to inhibit the growth of fungi increase up to 2-20 days depending on type of fungi. Production of fresh noodle added sodium benzoate 1,000 ppm and adjusted pH with citric acid to 3.5 and 4.0 were conducted and compared with two control noodles with and without added sodium benzoate. The extension of noodle shelf life to 15, 6, 4 and 2 days, respectively was detected. There was no significant difference in the sensory evaluation between noodle with and without adjusted pH to 4. This results will benefit to the noodle producer to prolong the shelf life of fresh noodle.